Analisis Perbedaan Daluwarsa dan Pelepasan Hak dalam Hukum Waris Ditinjau dari Kitab Undang-Undang Hukum Perdata - Putri Mutia; Nuzul Rahmayani (AHKAM, 2026)
Although studies on daluwarsa have been widely conducted, research that specifically unpacks the ambiguity between daluwarsa and pelepasan hak in civil inheritance disputes remains limited, even though these are two legal institutions that are frequently conflated yet carry very different legal consequences in practice. This study aims to analyze the fundamental differences between daluwarsa (verjaring) and pelepasan hak (rechtsverwerking) in the Kitab Undang-Undang Hukum Perdata (KUHPerdata) and to examine their implications for the legal standing of heirs. The research employs a normative juridical method with a prescriptive and sui generis approach. Data were collected through literature study of regulations and scholarly works, as well as analysis of Decision No. 12/Pdt.G/2022/PN Pal and Supreme Court Cassation Decision No. 4866 K/Pdt/2024. The results show that daluwarsa operates mechanistically based on the passage of time, whereas pelepasan hak requires an element of awareness and volition on the part of the heirs, such that judicial error in distinguishing between these two institutions may eliminate the heirs’ absolute rights in the name of administrative certainty. The study concludes that an in-depth analysis of the boundaries, characteristics, and consequences of each concept of daluwarsa and pelepasan hak is crucial to clarifying the legal standing of heirs in inheritance disputes under the KUHPerdata. The implications of this research contribute to legal practice by guiding practitioners in applying more humane substantive justice in inheritance cases.